Electronic Textile from Lyocell and Very Few Layer Graphene: Studies and Review - Aminati, Ikha Setya; Amri, Amun; Amri, Evelyn (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2022)
Electronic textiles (e-textiles) are generally made by coating fabrics with conductive particles to impart conductive and electromagnetic properties to textile fibers and filaments. E-textile can be made by several methods, such as